1-Deoxynojirimycin with theaflavins ameliorates high-fat diet-induced insulin resistance in mice by modulating the gut microbiota - Di, Qiannan; Yang, Ting; Zhao, Yiwen; Li, Wenqing; Qu, Chunbo; Zhang, Jingyi; Zhu, Yichun; Song, Chenyang; Na, Lixin (Frontiers in Nutrition, 2026)
BackgroundThis study investigated the ameliorative effects of combined 1-DNJ and TFs on IR in mice through gut microbiota modulation.MethodsAn HFD-induced IR model was established in male mice, which were subsequently divided into Control, Model, 1-DNJ (200 mg/kg·bw/day), TFs (100 mg/kg·bw/day), and 1-DNJ + TFs (200 + 100 mg/kg·bw/day) groups for daily oral administration over 11 consecutive weeks. The ameliorative effects were evaluated by examining biochemical parameters in serum and histopathological changes in the liver pancreatic and colon. Mechanistic insights were elucidated through 16S rRNA gene sequencing of fecal samples and untargeted metabolomics analysis of intestinal contents.ResultsInterventions with 1-DNJ, TFs, or thecombination effectively reduced blood glucose levels and improved insulin sensitivity. The combined treatment demonstrated superior efficacy, decreasing circulating levels of LPS, IL-6, and TNF-α, alleviating hepatic lipid accumulation, and reducing colon tissue barrier damage. Furthermore, the combined intervention profoundly modulated the gut microbiota, characterized by an increased abundance of beneficial bacteria (e.g., Muribaculaceae, Lachnospiraceae_NK4A136_group, Alloprevotella) and a reduction in harmful genera (e.g., Roseburia, Intestinimonas). These microbial shifts were concomitantly associated with significant alterations in intestinal metabolic pathways, including sphingolipid metabolism, necroptosis, glycerophospholipid metabolism, the pentose phosphate pathway, pentose and glucuronic acid interconversion, and tyrosine metabolism.ConclusionThe combined administration of 1-DNJ and TFs demonstrated superior efficacy in ameliorating HFD-induced IR compared to individual components, with gut microbiota modulation playing a pivotal role. These findings position 1-DNJ and TFs as promising natural candidates for functional food development targeting metabolic health.